(untitled) (Materiali di Estetica. Terza serie, 2017)
This Essay examines the relationship between Joseph und seine Brüder written by Thomas Mann and the Rabbinic Literature. In particular, the attention is focused on some Midrashic tales related to the story of Patriarch Joseph and his family and the way the German writer has reworked them in his tetralogy.